COMPUTER VISION SYNDROME–A PERSPECTIVE ON ASSESSMENT AND INTERVENTION - MADHURI, JAMPANA; IKRAM, SYEDA SADIYA; PURI, SANJEEV KUMAR (International Journal of Current Pharmaceutical Research, 2022)
Objective: The aim of the study was to assess the common symptoms, and its associated factors and to identify its ocular morbidity among them due to prolonged use of digital devices. Methods: A random sampling technique are used to calculate the sample size of 278. The questionnaire includes computer vision syndrome symptoms and factors associated with Computer Vision Syndrome development. Results: A total of 278 health care students participated in this study. The mean age of health care students was 20.68 y±2.51 standard deviation and the range was between 18-25 y. 40.6% were males and 59.3% were females. Among digital devices, 85.9% of student’s use mobile phones frequently, 61.8% spent continuously on digital devices and had a higher risk of developing Computer Vision Syndrome, 40.2% Students were aware of 20-20-20 rule, 37% were aware of using digital devices at 40-75 cm, in pre-assessment. Thereby providing awareness and knowledge by showing them awareness video helps to improve the results in post-assessment. Conclusion: There was a high prevalence of Computer Vision Syndrome symptoms among health care students in pre-assessment which was reduced in post-assessment. Thereby health care students who have knowledge on their eye care helps to prevent vision problems and it is also helpful for the people who are already having symptoms and ergonomic practices. So, they may consult the doctor without neglecting their visual problems.